Genetic testing in psychiatry, the perceptions of healthcare workers and patients: a mini review - Kyriakos I. Ioannou; Anastasia Constantinidou; Andreas Chatzittofis; Andreas Chatzittofis (Frontiers Media S.A., 2024)
BackgroundGenetic testing in psychiatry has gained attention, raising questions about its application and impact. Understanding stakeholders' perspectives, including healthcare providers and patients, is vital for informed policy development. The aim of this systematic review was to focus on the perceptions and concerns of patients and healthcare workers in psychiatry regarding the use of genetic testing.MethodsWe conducted a systematic review following PRISMA guidelines, for the period 1/2/2014, to 1/1/2024, via PubMed and Embase databases identifying 50 articles in total. After excluding duplicates (n = 12), 38 articles went through screening. After careful full-text article assessment for eligibility and applying the inclusion and exclusion criteria, only fifteen (n = 15) of the articles were included.ResultsAmong 15 selected studies involving 3,156 participants (2,347 healthcare professionals; 809 patients), thematic analysis identified four primary themes: Organizational-implementation concerns, Ethical Considerations, Concerns on changes in clinical praxis, and Legal implications. Despite these concerns, seven out of eleven studies indicated that healthcare workers viewed genetic testing in psychiatry positively. Patients' perspectives varied, with two of the four studies reflecting positive attitudes. No pervasive negative sentiment was observed.ConclusionOur review highlights the multidimensional perspectives of healthcare professionals and patients surrounding the application of genetic testing in psychiatry. These considerations need to be addressed to facilitate the implementation of genetic testing in clinical praxis in psychiatry. Further research is needed for validation of the results and to guide policies and clinicians in the integration of genetic testing into mental healthcare practice.